Between science and penal populism. A few comments on legal socialization in the context of Polish regulations on sexual crimes - Gaczoł, Klaudia (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The aim of the article is to analyze the phenomenon of legal socialization in the context of Polish regulations of sexual crimes. It will allow ascertaining whether the legislative actions undertaken meet the current social needs and above all whether they are truly effective. Legal awareness and internalization of values represented by applicable legal norms have fundamental significance in this process. The citizens’ attitude to the state penal system is the most important phenomenon, which is inextricably linked to ever-evolving views on punishment. It is worth considering whether the legal socialization really matters to the social perception of law and the level and type of its social legitimacy. This issue seems to be particularly interesting especially due to the thesis of the ‘crisis of law’ formulated for years in Poland and the lack of its scientific legitimacy. The influence of media on social attitudes, shaping stereotypes about the operation of the law and the justice system as well as the penal-populist rhetoric, which additionally deepens the alienation of the scientific community is also important for the phenomenon discussed here.